Finansal Yatırım Analizi Yöntemi İle Gayrimenkul Projelerinde Küresel Kriz Risklerinin Azaltılması - Sarıboyacıyan, Ketrin Aylin (Fen Bilimleri Enstitüsü, 2009)
Türkiye’de 2005 yılı itibariyle, gayrimenkul sektörü verileri sürekli yükselen bir eğri çizerken, küresel kriz ile önce duraklama, daha sonra gerileme dönemine geçmiştir. Gayrimenkul sektöründeki gelişmelerin devam edeceği varsayımıyla geliştirilen projeler sonucu, arz artmış ancak kriz nedeniyle talep düşmüş, özellikle konut projelerinde satış hızının, buna bağlı olarak da satış fiyatının düşmesine neden olmuştur. Böylelikle elde edilen gelir, gideri karşılayamaz bir hal almış, bankacılık sektörünün de krizden etkilenmiş olmasından dolayı finansman ihtiyacını karşılayamayınca, inşaat aşamasında duran projelerin artışı kaçınılmaz olmuştur. Bu çalışma kapsamında, riskli projelerin saptanabilmesi için öncelikle kriz ortamı tanımlanmış ve 2008 yılı ABD’de başlayan mortgage krizinin gayrimenkul sektörüne olan etkileri incelenmiş, İzmir İli içerisinde belirlenen bir çalışma alanında, finansal yatırım analizi kapsamında risk değerlendirmesi yapılmıştır.

As of 2005, all indicators of real estate sector was in a continuously rising trend in Turkey. With the start of the global economic crises, first, trend started to become flat and then moved to a period of decline. Real estate development projects, which have been planned with the assumption of continuous positive trend of real estate sector, have increased the supply and as opposite to this uptrend, due to the crises, demand have decreased tremendously. Mainly this drop on demand have caused a decline on sales rates and related sales prices. In this manner, total revenue started not to meet the total cost of projects. Also banking sector which is affected by the crises have started not to meet financial requirements. With all these reasons, increase on the number of projects which are having to be stopped was inevitable. Within the scope of this project, in order, economic crises will be defined, impact of 2008 Mortgage crises held in United States of America on the real estate industry will be analysed and risk assessment will be applied by using financial investment analysis.
Reducing Risks Of Global Financial Crysis’ By Using Financial Investment Analysis Method On Real Estate Development Projects
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2009
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2009
Keywords: Gayrimenkul Geliştirme; Ekonomik Kriz; Risk Değerlendirmesi; Fizibilite; İzmir; Real Estate Development; Economic Crisis; Risk Analysis; Financial Investment Analysis; Izmir